Food Logistics Preparedness and Community Health Resilience in Flood-Prone Areas: The Role of Individual, Structural, and Environmental Factors - Alfiyani, Lina; Kusparlina, Eny Pemilu; Dewi, Lenny Puspita; Maulia, Risma Resty (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Food security and food logistics preparedness are essential components in strengthening community health resilience in flood-prone areas. Recurrent flooding disrupts food distribution systems and increases the risk of malnutrition and environment-related diseases, highlighting the need for evidence-based disaster preparedness strategies. This study aimed to analyze the influence of individual factors (age, sex, and education level), structural factors (food distribution effectiveness, food logistics preparedness, and policy support), and environmental factors (infrastructure and health facilities) on community health resilience in flood-affected areas. A quantitative study with a cross-sectional design was conducted. Data were collected through structured questionnaires administered to community members and stakeholders, as well as document reviews of disaster management and food distribution reports. Community health resilience was directly influenced by age, sex, education level, and the effectiveness of food distribution. In addition, indirect effects were observed from food logistics preparedness, environmental factors, policy support, and the availability of health facilities. In conclusion, community health resilience in flood-prone areas is shaped by the interaction of individual, structural, and environmental factors. Strengthening food logistics systems and policy support is therefore essential to enhance community health resilience during flood disasters.Keywords: flood-prone areas; community health resilience; food logistics preparedness; food distribution effectiveness; policy support